Exosomes from human mesenchymal stem cells conduct aerobic metabolism in term and preterm newborn infants. Issue 4 (11th December 2015) - Panfoli, Isabella; Ravera, Silvia; Podestà, Marina; Cossu, Claudia; Santucci, Laura; Bartolucci, Martina; Bruschi, Maurizio; Calzia, Daniela; Sabatini, Federica; Bruschettini, Matteo; Ramenghi, Luca Antonio; Romantsik, Olga; et al.
Abstract : Exosomes are secreted nanovesicles that are able to transfer RNA and proteins to target cells. The emerging role of mesenchymal stem cell (MSC) exosomes as promoters of aerobic ATP synthesis restoration in damaged cells, prompted us to assess whether they contain an extramitochondrial aerobic respiration capacity. Exosomes were isolated from culture medium of human MSCs from umbilical cord of ≥37‐wk‐old newborns or between 28‐ to 30‐wk‐old newborns ( i.e., term or preterm infants). Characterization of samples was conducted by cytofluorometry. Oxidative phosphorylation capacity was assessed by Western blot analysis, oximetry, and luminometric and fluorometric analyses. MSC exosomes express functional respiratory complexes I, IV, and V, consuming oxygen. ATP synthesis was only detectable in exosomes from term newborns, suggestive of a specific mechanism that is not completed at an early gestational age. Activities are outward facing and comparable to those detected in mitochondria isolated from term MSCs. MSC exosomes display an unsuspected aerobic respiratory ability independent of whole mitochondria. This may be relevant for their ability to rescue cell bioenergetics. The differential oxidative metabolism of preterm vs. term exosomes sheds new light on the preterm newborn's clinical vulnerability. A reduced ability to repair damaged tissue and an increased capability to cope with anoxic environment for preterm infants can be envisaged.—Panfoli, I., Ravera, S., Podestà, M., Cossu, C., Santucci, L., Bartolucci, M., Bruschi, M., Calzia, D., Sabatini, F., Bruschettini, M., Ramenghi, L. A., Romantsik, O., Marimpietri, D., Pistoia, V., Ghiggeri, G., Frassoni, F., Candiano, G. Exosomes from human mesenchymal stem cells conduct aerobic metabolism in term and preterm newborn infants. FASEB J. 30, 1416–1424 (2016). www.fasebj.org